Development of a Moderated Online Intervention to Treat Social Anxiety in First-Episode Psychosis - McEnery, Carla; Lim, Michelle H.; Knowles, Ann; Rice, Simon; Gleeson, John; Howell, Simmone; Russon, Penni; Miles, Chris; D’Alfonso, Simon; Alvarez-Jimenez, Mario (Frontiers in Psychiatry, 2019)
Background: It is well established that social anxiety disorder (SAD) is a significant clinical problem for individuals with a psychotic disorder. Comorbid social anxiety in individuals with psychosis has been associated with poorer premorbid functioning, increased depression and a reduced quality of life. Cognitive behavior therapy (CBT) is recommended for people with psychosis as a first-line psychological treatment; however, its focus and evaluation primarily revolves around reducing psychotic symptoms and not necessarily targeting comorbid social anxiety symptoms. We developed a novel online social cognitive-behavioral intervention (entitled EMBRACE) specifically designed to treat social anxiety symptoms in first episode psychosis (FEP). Methods: The key clinical and engagement features of the intervention were established through integrating evidence-based material derived from (1) CBT-based treatment models for SAD, (2) relevant literature findings related to psychosis and its clinical correlates (e.g., shame, social rank, and its relationship with social anxiety and paranoia), (3) feedback from youth focus groups in order to inform a user-centered intervention design, and (4) a highly multidisciplinary collaborative development approach to design therapy comics. Results: A detailed description of the final version of the twelve-week online social intervention to treat social anxiety in FEP is presented. Conclusion: The EMBRACE intervention was designed to provide young people with the necessary skills and confidence to overcome social anxiety within a supportive, safe online space. By design, it allows young people the opportunity to practice their newly learnt skills to connect with others and in doing so, learn to embrace their true authentic selves.